Identification of Novel and Noninvasive Biomarkers of Acute Cellular Rejection After Liver Transplantation by Protein Microarray. Issue 12 (December 2016) - Okubo, Keita; Wada, Hiroshi; Tanaka, Atsushi; Eguchi, Hidetoshi; Hamaguchi, Masahide; Tomokuni, Akira; Tomimaru, Yoshito; Asaoka, Tadafumi; Hama, Naoki; Kawamoto, Koichi; Kobayashi, Shogo; Marubashi, Shigeru; et al.
Abstract : Background: Acute cellular rejection (ACR) is one of the main factors in transplanted organ failure in liver transplantation. A precise marker for diagnosing or predicting rejection is not currently available; therefore, invasive liver biopsy is standard procedure. To develop a noninvasive method for precise diagnosis of ACR, we evaluated autoantibodies from patient sera as potential biomarkers using protein microarrays (seromics). Methods: Sera from hepatitis C virus–positive ACR patients were compared to three hepatitis C virus cirrhosis control groups and healthy volunteers. The control groups consisted of 2 no-ACR groups obtained on postoperative day 28 and 1 year after transplantation and a preoperative group obtained 1 day before transplantation. For validation, we evaluated whether the candidate antibodies can distinguish ACR from other types of liver dysfunction after liver transplantation using enzyme-linked immunosorbent assay. Results: Seromic analysis by weighted average difference (WAD) ranking and Mann-Whitney U test revealed a significant increase of 57 autoantibodies in the sera of ACR patients with liver dysfunction. Among the 57 candidates, autoantibodies to charged multivesicular body protein 2B, potassium channel tetramerization domain containing 14, voltage gated subfamily A regulatory beta subunit 3, and triosephosphate isomerase 1 were regarded as potential biomarkers of ACR after liver transplantation. Using 20 ACR patients with variable backgrounds for validation, the autoantibodies to charged multivesicular body protein 2B and triosephosphate isomerase 1 were significantly increased in ACR patients compared to other control groups. Conclusions: A panel of autoantibodies identified by seromics as potential noninvasive biomarkers was clinically useful for diagnosing ACR after liver transplantation.